PENGARUH KUALITAS LAYANAN DAN CITRA PERUSAHAAN TERHADAP LOYALITAS NASABAH MELALUI KEPUASAN NASABAH SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA PT. BPR BANK DAERAH GUNUNGKIDUL) - Rizka Cahyani Hermawati; Ambar Lukitaningsih; Putri Dwi Cahyani (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
ABSTRACT This study aims to determine: 1) the effect of service quality on customer satisfaction at PT. BPR Bank Daerah Gunungkidul. 2) the effect of corporate image on customer satisfaction PT. BPR Bank Daerah Gunungkidul. 3) the effect of service quality on customer loyalty PT. BPR Bank Daerah Gunungkidul. 4) the effect of corporate image on customer loyalty PT. BPR Bank Daerah Gunungkidul and 5) the effect of customer satisfaction on customer loyalty PT. BPR Bank Daerah Gunungkidul.This research is a quantitative research, using descriptive analysis. The population in this study are customers of PT. BPR Bank Daerah Gunungkidul. The sampling technique used purposive sampling. Data collection was carried out using a questionnaire method in the form of a Google Form which was distributed to 105 customers of PT. BPR Bank Daerah Gunungkidul. The data analysis technique in this study used multiple linear regression.The results of the study show that the service quality variable influences customer satisfaction. corporate image variable has no effect on customer satisfaction. Service quality variable influences customer loyalty. Corporate image variable has no effect on customer loyalty and customer satisfaction variable has an effect on customer loyalty on PT. BPR Bank Daerah Gunungkidul.